GAYA PEMBUATAN KEPUTUSAN KARIER MAHASISWA BARU PROGRAM STUDI BIMBINGAN KONSELING UNIVERSITAS MUHAMMADIYAH SUMATERA UTARATAHUN AJARAN 2017-2018 - Erwita Ika Violina (Universitas Sultan Ageng Tirtayasa, 2018)
Career decision making style is individual characteristics in observing and responding to decision-making tasks, and acting in making decisions. The decisionmaking style is divided into three styles: rational, intuitive, and dependent. This study aims to describe the career decision making style of new students Guidance and CounselingMuhammadiyah University of North Sumatera academic year 2017-2018. The population in this study are 109 new students of guidance and counseling program of University of Muhammadiyah Sumatera Utara academic year 2017-2018, and all of population researched in this research. The instrument used in this study is the assessment of decision-making styles adapted from Harren's ACDM (1979). The results showed that 1. 38% of new students Guidance and Counseling Muhammadiyah University of North Sumatera have Rational career decision making style, 2. 35% of new students Guidance and Muhammadiyah University of North Sumatera have Dependen career decision making style, and 3 25% of new students Guidance and Counseling Muhammadiyah University of North Sumatera have intuitive career decision making style. Keywords: career decision making styles, new guidance and counseling students